Solvent system and method for chitin processing

By using a solvent system containing ionic liquid or deep eutectic solvent in chitin processing, combined with mechanical stirring and cold bath dispersion technology, the high cost and pollution problems in the existing methods are solved, and the production of high-quality chitin nanocrystals is achieved.

CN119677784APending Publication Date: 2025-03-21NEPTUNE NANOTECHNOLOGIES INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380058472.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-08
Filing Date
2023-08-08
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the existing chitin processing methods, although the acidic hydrolysis process can control the agglomeration problem, it still needs to be improved; while the use of ionic liquid methods can generate high-quality nanocrystals, it is costly and may introduce contamination.

Method used

A solvent system is adopted, comprising at least one ionic liquid or deep eutectic solvent, combined with inorganic alkali and water, the mixture is concentrated by mechanical stirring and boiling, and the concentrate is quickly dispersed into a cold bath, allowing amorphous chitin to precipitate and re-crystallize, and finally decontaminated and collect chitin.

Benefits of technology

The production of high-quality chitin nanocrystals is achieved, which avoids the excessive use of expensive ionic liquids, reduces costs and pollution risks, and retains the quality of nanocrystals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119677784A_ABST
    Figure CN119677784A_ABST
Patent Text Reader

Abstract

A chitin processing method comprises: dispersing nanocrystalline and amorphous chitin in a solvent system to form a mixture wherein the mixture has a solid-to-solvent ratio of not more than 7% by weight, the solvent system comprising: a first component comprising at least one ionic liquid; and at least one inorganic base; the second component comprises water, and the first component accounts for not more than 10% of the volume of the solvent system; the method further comprises: mechanically stirring and / or boiling the mixture; concentrating the mixture to increase the ratio of solids to the solvent system; quickly dispersing the concentrated mixture into a cold bath of water and / or a water miscible solvent; and decontaminating and collecting the basically retained and newly crystallized chitin. Other methods, as well as solvent systems for use therewith, are also provided.
Need to check novelty before this filing date? Find Prior Art

Description

Cross-references

[0001] This application claims priority to U.S. Provisional Patent Application Serial No. 63 / 395,915 filed on August 8, 2022, the contents of which are incorporated herein by reference. Technical Field

[0002] The following mainly relates to methods of chitosan processing, and solvent systems used for this purpose. Background Art

[0003] Nanoparticles are particles having one or more dimensions between 1 and 100 nanometers (nm). Nanoparticles of a particular material can exhibit properties and behaviors that are significantly different from larger particles of the same material, primarily because a relatively high percentage of their atoms are located on the surface, providing a very large surface area relative to their size.

[0004] Nanocomposites are multiphase materials found in nature or artificially made, in which one phase is nanoparticles. For example, solid nanocomposites include nanoparticles dispersed in a bulk solid matrix. Due to the unique physical properties of nanoparticles, a small proportion of nanoparticles can produce a significant macroscopic effect on the bulk solid matrix. Therefore, it is of great significance to manufacture nanocomposites with nanoparticles to impart beneficial macroscopic mechanical, electrical, optical, dielectric, thermal, antibacterial or other effects.

[0005] Nanofibrils or nanowhiskers are nanoparticles with a crystalline rod-like structure. Chitosan nanowhiskers consist of crystalline polysaccharides with a diameter of about 10 nanometers and a length of about 200 nanometers to about 500 nanometers, which are an abundant, biodegradable and non-toxic structural polysaccharide material, chitosan, found in crustaceans such as shrimp and crabs. Chitosan nanowhiskers are suitable for nanocomposites because they can impart desirable mechanical and antimicrobial effects while also being biodegradable, abundant and non-toxic.

[0006] In nature, chitosan contains amorphous and crystalline chitosan, as well as a variety of other components such as proteins. In order to be applied to nanocomposites, most of the individual chitosan nanowhiskers need to be extracted or produced from chitosan so that the individual nanowhiskers can be dispersed throughout the matrix. Therefore, it is necessary to process the chitosan material so that only individual chitosan nanowhiskers can be extracted or produced, and very little or no agglomerated chitosan is contained in the individual chitosan nanowhiskers.

[0007] Known acidic hydrolysis processes can produce chitosan nanowhiskers from chitosan materials. For example, U.S. Patent No. 9,169,376 to Guan discloses a method for processing chitosan, including forming a non-colloidal mixture consisting essentially of chitosan and hydrochloric acid to hydrolyze the chitosan; controlling the conditions of the mixture to slow the hydrolysis when the mixture becomes substantially colloidal; dialyzing the substantially colloidal mixture to produce a processed colloidal mixture consisting essentially of water and crystalline chitosan; and reducing the amount of agglomerated crystalline chitosan and water in the processed colloidal mixture to obtain a chitosan nanowhiskers gel in which the amount of agglomerated and amorphous chitosan has been reduced. Although known acidic hydrolysis processes, such as the process disclosed in the '376 patent, can provide reasonably effective control over the agglomeration problem by precisely timing the hydrolysis, improvements are still needed.

[0008] Other methods used to process raw chitin to produce non-agglomerated chitin nanowhiskers require fully dissolving the raw chitin in an ionic liquid solvent and regenerating the nanocrystals from the fully dissolved chitin. Since they are essentially built "from the ground up", such regenerated nanocrystals are of very high quality. However, known methods of processing chitin using ionic liquids can be extremely expensive, especially due to the cost of the ionic liquids themselves. In addition, ionic liquid residues can introduce contamination that can adversely affect sensitive applications. Summary of the invention

[0009] According to one aspect, a method for processing chitosan is provided, comprising: dispersing nanocrystalline and amorphous chitosan in a solvent system to form a mixture, wherein the ratio of solid to solvent in the mixture is no more than 7% by weight, and the solvent system comprises: a first component comprising: at least one ionic liquid; and at least one inorganic base; and a second component comprising water, wherein the first component accounts for no more than 10% by volume of the solvent system; the method further comprises: mechanically stirring and / or boiling the mixture; concentrating the mixture to increase the ratio of solid to solvent system; rapidly dispersing the concentrated mixture into a cold bath of water and / or a water-miscible solvent; and decontaminating and collecting substantially retained and newly crystallized chitosan.

[0010] In one example, the solvent system comprises a plurality of ionic liquids.

[0011] In one example, each of the plurality of ionic liquids is selected from the group consisting of 1-ethyl-3-methylimidazolium acetate, 1-butyl-3-methylimidazolium chloride, and 1-propenyl-3-methylimidazolium bromide.

[0012] In one example, the second component further comprises alcohols.

[0013] In one example, the alcohol is selected from the group consisting of ethanol, methanol, isopropanol, tert-butyl alcohol, 2-propanol, and benzyl alcohol.

[0014] In one example, the at least one inorganic base is selected from the group consisting of sodium hydroxide, calcium iodide, calcium chloride, calcium bromide, lithium thiocyanate, and combinations thereof.

[0015] In one example, rapidly dispersing the concentrated mixture into a cold bath of water and / or a water-miscible solvent includes dispersing using a nozzle spray or a mist spray.

[0016] According to another aspect, a method for processing chitosan is provided, comprising: dispersing nanocrystalline and amorphous chitosan in a solvent system to form a mixture, wherein the solid to solvent ratio of the mixture is no more than 7% by weight, and the solvent system comprises: a first component, comprising: at least one deep eutectic solvent; and at least one inorganic base; and a second component, comprising water, wherein the first component accounts for no more than 10% by volume of the solvent system; the method further comprises: mechanically stirring and / or boiling the mixture; concentrating the mixture to increase the solid to solvent ratio; rapidly dispersing the concentrated mixture into a cold bath of water and / or a water-miscible solvent; and decontaminating and collecting substantially retained and newly crystallized chitosan.

[0017] In one example, the solvent system comprises a plurality of deep eutectic solvents.

[0018] In one example, the second component further comprises alcohols.

[0019] In one example, the alcohol is selected from the group consisting of ethanol, methanol, isopropanol, tert-butyl alcohol, 2-propanol, and benzyl alcohol.

[0020] In one example, the at least one inorganic base is selected from the group consisting of sodium hydroxide, calcium iodide, calcium chloride, calcium bromide, lithium thiocyanate, and combinations thereof.

[0021] According to another aspect, a solvent system is provided for at least half-dissolving amorphous chitosan while substantially retaining nanocrystalline chitosan, the solvent system comprising: a first component comprising: at least one ionic liquid; and at least one inorganic base; and a second component comprising water, wherein the first component accounts for no more than 10% of the volume of the solvent system.

[0022] According to another aspect, a solvent system is provided for at least half-dissolving amorphous chitosan while substantially retaining nanocrystalline chitosan, the solvent system comprising: a first component comprising: at least one deep eutectic solvent; and at least one inorganic base; and a second component comprising water, wherein the first component accounts for no more than 10% by volume of the solvent system.

[0023] According to another aspect, a method is provided, comprising: receiving a mixture of nanocrystalline chitosan and amorphous chitosan; forming a combination of the mixture and a solvent system, the solvent system being configured to at least semi-dissolve the amorphous chitosan while substantially retaining the nanocrystalline chitosan; concentrating the combination to increase the solid to solvent ratio; rapidly dispersing the concentrated combination into a cold bath to precipitate the at least semi-dissolved amorphous chitosan and then recrystallize along the plane of the substantially retained nanocrystalline chitosan; and decontaminating the substantially retained and recrystallized chitosan and collecting it from the cold bath. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The embodiments will be further described in detail with reference to the drawings, wherein:

[0025] Figure 1 It is a flow chart of a chitosan processing method.

[0026] Figure 2 is a flow chart of another chitin processing method. DETAILED DESCRIPTION

[0027] The input to a new chitosan processing method could be the output of a previous process, such as an acid hydrolysis process, which itself could provide chitosan nanocrystals with amorphous regions attached to crystalline regions.

[0028] These inputs can then be treated using a specific solvent system that may contain a combination of one or more ionic liquids, and other solvent components in very small but precisely defined concentrations (<10% by volume), with the remainder of the solvent system being water. This treatment is also controlled by temperature, time, and mechanical agitation.

[0029] Although not attempted at the time of this writing, it is contemplated that, based on the findings disclosed herein and based on their chemical similarity to ionic liquids, one or more deep eutectic solvents could be used in place of such ionic liquids, thereby allowing chitin to be processed in the same manner as the ionic liquids disclosed herein.

[0030] This treatment converts the amorphous chitin phase (solid) into a semi-dissolved state, in which the amorphous chitin polymer chains can move freely. Importantly, this solvent system treatment does not affect the state of the crystalline phase. This is believed to be due to the tightly packed crystal structure and the different expansion behavior from the amorphous phase, which makes the interaction between this solvent system and the amorphous phase chitin different from the interaction between the crystalline phase chitin.

[0031] The solvent can then be squeezed out using centrifugation, membrane filtration or any other method. The result is then a very concentrated concentration of chitin nanocrystals in an aqueous solvent, with "tails" of semi-dissolved amorphous chitin polymer chains attached to them in a mobile state.

[0032] This entire mixture can then be placed under new conditions that allow the semi-dissolved amorphous chitin polymer chains ("tails") to solidify rapidly. By carefully controlling this process, the polymer chains will tend to solidify in an orderly manner along the crystal planes of nearby chitin nanocrystals. Advantageously, this effectively utilizes the existing nanocrystals that remain in the solvent system when the amorphous chitin is dissolved or semi-dissolved as seed crystals.

[0033] This provides high-quality nanocrystals without amorphous regions because the previously amorphous phase chitin has been recrystallized.

[0034] Figure 1 1 is a flow chart showing a method 10 for processing chitin according to the present disclosure. In method 10, nanocrystalline and amorphous chitin are dispersed in a solvent system to form a mixture, wherein the ratio of solids to solvent in the mixture does not exceed 7% by weight (step 100). It should be understood that in some embodiments, the solvent system may include a first component comprising: at least one ionic liquid and at least one inorganic base; and a second component comprising water, wherein the first component accounts for no more than 10% by volume of the solvent system.

[0035] In addition, in method 10, the mixture is mechanically stirred and / or boiled (step 200), thereby concentrating the mixture to increase the ratio of solid to solvent system (step 300). The concentrated mixture is then quickly dispersed in a cold water bath and / or a water-miscible solvent (step 400), and the substantially retained and newly crystallized chitosan is decontaminated and collected (step 500).

[0036] The main advantage of this method is that it still uses processes such as acid hydrolysis to output amorphous and nanocrystalline chitin as input for the new method. Processes such as acid hydrolysis are efficient, low-cost, and scalable. In addition, the method itself uses very small amounts of expensive complex solvents and other materials to control cost and pollution issues. However, the new method shows that the chitin nanocrystals produced are almost equivalent in quality to the expensive method of growing all crystals from the bottom up.

[0037] The output of this new method can be used as a new nanocrystal benchmark for new applications such as polymer masterbatches and epoxy concentrates. Specific embodiments

[0038] 1. A known HCl (hydrochloric acid) acid hydrolysis process was performed to produce chitosan nanocrystals (nanowhiskers) with some agglomerates and amorphous chitosan attachments.

[0039] 2. It can optionally be lyophilized (freeze dried) to form a powder before subsequent processing steps.

[0040] It is understood that the output of step 1 (and optionally, step 2) above will be a semi-good chitosan nanocrystalline material, but with some significant agglomerates and amorphous phase attachments. It is understood that the HCl acid hydrolysis process is an example of a process that can produce semi-good chitosan nanocrystallines but with agglomerates and amorphous phase attachments. The present disclosure is not particularly limited to receiving and operating on the output of the HCl acid hydrolysis process, as the following steps can also be successfully used to process the output of other processes that can produce chitosan nanocrystallines with agglomerates and amorphous phase attachments.

[0041] 3. Disperse chitosan nanocrystals in a water solvent having the following composition: Ionic liquid group: (l-ethyl-3-methylimidazolium acetate, l-butyl-3-methylimidazolium chloride, l-propenyl-3-methylimidazolium bromide) (Note: it is expected that deep eutectic solvents could be used in place of ionic liquids as they are chemically similar, but as of this writing, this has not been attempted) At least one inorganic base: (e.g., selected from the group consisting of sodium hydroxide, calcium iodide, calcium chloride, calcium bromide, and lithium thiocyanate) Additional solvents: (N,N-dimethylacetamide, LiCl, CaCl2) When the total volume of the above solvents does not exceed 10% by volume (0.1% to 10%), the remaining solvents are water and alcohols. Alcohols: (ethanol, methanol, isopropanol, tert-butyl alcohol, 2-propanol, benzyl alcohol) The ratio of solid to solvent is not more than (including not more than) 7% by weight.

[0042] It has been observed that ionic liquids disrupt hydrogen bonds on chitin, while inorganic bases and additional solvents aid in this disruption. Additionally, alcohols can adjust the polarity of the solvent to better match that of chitin. At the time of this writing, two acetate-based ionic liquids have been tested, along with only 1 additional solvent and 1 family of inorganic bases. Different combinations and amounts of these ingredients (e.g., less ionic liquid, or more additional solvent, or more inorganic base) may work as well or better than the above combinations. The amount of alcohols depends on their relative polarities, so the less polar, the less alcohol is needed.

[0043] 4. The entire mixture is then boiled under vigorous mechanical stirring for 15 to 90 minutes.

[0044] The effect of these steps is to bring the amorphous phase of chitosan into a semi-dissolved state, in which the polymer chains are fully swollen and mobile, but do not interfere with the nanocrystalline phase itself.

[0045] 5. The mixture is then concentrated as far as possible, for example by filtration (in order to maintain the solvent ratio during the concentration process) or by evaporation by boiling.

[0046] 6. The concentrated mixture is then dispersed rapidly into a cold water bath. It is anticipated that other water miscible solvents may also be used in place of, or in combination with, water. This can be most advantageously accomplished rapidly and with small droplet sizes by using a nozzle spray or a mist spray.

[0047] This concentration followed by rapid dispersion is intended to quickly eliminate conditions that would cause the amorphous chitin to semi-dissolve or completely dissolve. The inventors have observed that chitin has a natural tendency to crystallize, and if possible, it will crystallize along existing crystal planes rather than nucleate new crystals. In other words, it minimizes Gibbs free energy. Advantageously, the corresponding portion of the amorphous chitin will dissolve or semi-dissolve, while the original chitin crystals retained in the solvent will essentially serve as seed crystals, and the originally amorphous chitin will grow additional crystalline layers thereon.

[0048] 7. The chitosan dispersion bath is then washed and / or filtered to remove possible chemical residues. The mixture is then concentrated into a hydrogel, dried, and / or loaded into other solvents or carrier resins for downstream processing and / or formation of nanocomposites.

[0049] The above method receives a chitosan material including nanocrystals (nanowears) that may have some agglomerates and amorphous chitosan attachments, uses a solvent system to dissolve or semi-dissolve the amorphous chitosan while retaining the chitosan in nanocrystalline form, and then controls the conditions in the solution so that the dissolved or semi-dissolved amorphous chitosan quickly leaves the solution (precipitates) and immediately crystallizes along the crystal faces of the retained nanocrystalline form. It should be understood that variations of the above method, such as using more or less or different ionic liquids, using deep eutectic solvents, using more or less additional solvents, using more or less inorganic bases, boiling the mixture without mechanical stirring, boiling the mixture without boiling and only mechanical stirring, or boiling and / or mechanical stirring for longer or shorter times or intervals, and other variations to this basic process, can partially or completely successfully convert amorphous chitosan into crystalline chitosan, while completely retaining the chitosan that was originally in the crystalline phase so that it remains intact as a seed crystal for forming new crystals.

[0050] There are several possible alternatives.

[0051] For example, in Figure 1 In the illustrated method 10, the solvent system may include a first component comprising: at least one deep eutectic solvent; and at least one inorganic base; and a second component comprising water, wherein the first component accounts for no more than 10% by volume of the solvent system.

[0052] In addition, based on the principles disclosed herein, a solvent system is formulated and applied to advantageously act on chitosan to achieve the purposes disclosed herein, and similar but different methods for processing chitosan can also be provided. For example, referring to Figure 2 Method 510 includes receiving a mixture of nanocrystalline chitosan and amorphous chitosan (600). Forming a combination of the mixture and a solvent system configured to at least partially dissolve the amorphous chitosan while substantially retaining the nanocrystalline chitosan (step 700). Concentrating the combination to increase the solid to solvent ratio (step 800), and rapidly dispersing the concentrated combination into a cold bath to cause precipitation of the at least partially dissolved amorphous chitosan, followed by recrystallization along the plane of the substantially retained nanocrystalline chitosan (step 900). Decontaminating the substantially retained and recrystallized chitosan and collecting it from the cold bath (step 1000).

Claims

1. A method for processing chitin, comprising: Nanocrystalline and amorphous chitosan are dispersed in a solvent system to form a mixture, wherein the ratio of solid to solvent in the mixture is not greater than 7% by weight, and the solvent system comprises: A first component comprising: at least one ionic liquid; and at least one inorganic base; as well as a second component comprising water, wherein the first component accounts for no more than 10% by volume of the solvent system, The method further comprises: mechanically stirring and / or boiling the mixture; concentrating the mixture to increase the ratio of solids to solvent system; rapidly dispersing the concentrated mixture into a cold bath of water and / or a water-miscible solvent; and The substantially retained and newly crystallized chitin is decontaminated and collected.

2. The method of claim 1, wherein the solvent system comprises a plurality of ionic liquids.

3. The method of claim 2, wherein each of the plurality of ionic liquids is selected from the group consisting of 1-ethyl-3-methylimidazolium acetate, 1-butyl-3-methylimidazolium chloride, and 1-propenyl-3-methylimidazolium bromide.

4. The method of claim 1, wherein the second component further comprises an alcohol.

5. The method of claim 4, wherein the alcohol is selected from the group consisting of ethanol, methanol, isopropanol, tert-butyl alcohol, 2-propanol, benzyl alcohol.

6. The method of claim 1, wherein the at least one inorganic base is selected from the group consisting of sodium hydroxide, calcium iodide, calcium chloride, calcium bromide, lithium thiocyanate, and combinations thereof.

7. The method of claim 1, wherein the concentrated mixture is rapidly dispersed into a cold bath of water and / or a water-miscible solvent, including dispersing using a nozzle spray or a spray jet.

8. A method for processing chitosan, comprising: Nanocrystalline and amorphous chitosan are dispersed in a solvent system to form a mixture, wherein the ratio of solid to solvent in the mixture is not greater than 7% by weight, and the solvent system comprises: A first component comprising: at least one deep eutectic solvent; and at least one inorganic base; as well as a second component comprising water, wherein the first component accounts for no more than 10% by volume of the solvent system; The method further comprises: mechanically stirring and / or boiling the mixture; concentrating the mixture to increase the ratio of solids to solvent system; rapidly dispersing the concentrated mixture into a cold bath of water and / or a water-miscible solvent; and The substantially retained and newly crystallized chitin is decontaminated and collected.

9. The method of claim 8, wherein the solvent system comprises a plurality of deep eutectic solvents.

10. The method of claim 8, wherein the second component further comprises an alcohol.

11. The method of claim 10, wherein the alcohol is selected from the group consisting of ethanol, methanol, isopropanol, tert-butyl alcohol, 2-propanol, benzyl alcohol.

12. The method of claim 8, wherein the at least one inorganic base is selected from the group consisting of sodium hydroxide, calcium iodide, calcium chloride, calcium bromide, lithium thiocyanate, and combinations thereof.

13. A solvent system for at least half-dissolving amorphous chitosan while substantially retaining nanocrystalline chitosan, the solvent system comprising: A first component comprising: at least one ionic liquid; and at least one inorganic base; as well as a second component comprising water, The first component accounts for no more than 10% of the volume of the solvent system.

14. A solvent system for at least half-dissolving amorphous chitosan while substantially retaining nanocrystalline chitosan, the solvent system comprising: A first component comprising: at least one deep eutectic solvent; and at least one inorganic base; as well as a second component comprising water, The first component accounts for no more than 10% of the volume of the solvent system.

15. A method comprising: Receiving a mixture of nanocrystalline chitosan and amorphous chitosan; forming a combination of the mixture and a solvent system configured to at least semi-dissolve the amorphous phase chitin while substantially retaining the nanocrystalline phase chitin; concentrating the combination to increase the ratio of solids to solvent; rapidly dispersing the concentrated combination into a cold bath to precipitate the at least semi-dissolved amorphous chitin phase, followed by recrystallization along substantially retained planes of nanocrystalline chitin; as well as The substantially retained and recrystallized chitin was decontaminated and collected from the cold bath.

Citation Information

Patent Citations

  • Chitin nanowhisker composites and methods

    US9169376B2